Analise dos aspectos socioeconômicos e infraestruturais do assentamento casqueira I em Areia Branca/RN - Mota, Emiliane Melo Rodrigues (Universidade Federal Rural do Semi-Árido, 2019)
The work comprises a study about the socioeconomic and infrastructural aspects of the Casqueira I settlement, located in the city of Areia Branca, in Rio Grande do Norte. For this, a survey was necessary through the application of questionnaires with the residents of the community. In 1995 the villagers gathered and made a camp at the place where the settlement was built today, only two years later they gained land tenure and have been fighting ever since for more rights. Despite the improvements and living conditions of the residents, they now claim to have running water, a health clinic in the community and better working conditions in the countryside to enable them to earn a better income. Agriculture is the most important activity among the settlers, many developing it only for subsistence and those who negotiate their crops claim that the income is still insufficient to support their families, thus needing government benefits for this support. We understand that Agrarian Reform as it is written and documented is of prime importance for rural men and women, but in reality more commitment is needed from the competent bodies to actually provide decent conditions for the settlers. There is still a long trajectory of struggles for proper realization.
Monografia
Keywords: Assentamento; Infraestrutura; Social; Econômico; Reforma agrária; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO::EDUCACAO RURAL